The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1080/15428119891010424
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Exposure to Captan in Fruit Growing

Abstract: A series of studies investigated occupational exposure to pesticides among fruit growers in The Netherlands during spraying and reentry of orchards between 1990 and 1992 to identify and quantify determinants of exposure. Determinants of exposure are discussed as a starting point for hazard identification and control. Captan was used as a marker for exposure. Cabin use of the tractor was the most prominent determinant of dermal exposure during spraying. For respiratory exposure, factors related to preparation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…De Cock et al (1998a, 1998b reported that exposure intensity for orchard thinning is about twice that of orchard harvesting or pruning. This may be due to the workers' substantial physical contact with tree foliage or to the high dermal absorption of pesticides such as azinphosmethyl .…”
Section: Discussionmentioning
confidence: 99%
“…De Cock et al (1998a, 1998b reported that exposure intensity for orchard thinning is about twice that of orchard harvesting or pruning. This may be due to the workers' substantial physical contact with tree foliage or to the high dermal absorption of pesticides such as azinphosmethyl .…”
Section: Discussionmentioning
confidence: 99%
“…De Cock et al measured levels of cutaneous contamination ranging from 0.47 to 48.6 mg/h/m 2 , depending on pad location and type of spraying equipment. 34 Few models are currently available to simultaneously consider a set of quantitative (amount handled, duration of exposure, etc) as well as qualitative (protection used) exposure parameters. The UK-POEM is among those used for registration purposes in European countries.…”
Section: Figurementioning
confidence: 99%
“…Two used the same pesticide (captan) [Zweig et al 1985;De Cock, 1998a,b], but the application rate was available only for one [Zweig et al, 1985]. Ratio of pesticides on hands and forearms was 7.2 [Zweig et al,1983] DFR Body r 0.90 [Zweig et al,1985] DFR Body r 0.50^0.57, reported as a range [McCurdy et al,1994] DFR Hands,wrists, arm, Statistically significant [De Cock et al,1998b] forehead DFR Estimated whole body Graphical representation showed body exposure increased with DFR. Using only the ®rst study for captan [Zweig et al, 1985], the exposure intensity was normalized for the amount of pesticide applied.…”
Section: Assessment Of Farmworkers' Exposure Intensitymentioning
confidence: 99%